Effectiveness Of Layer Leaves In Reducing Uric Acid Levels - Putri Reni; Dahlia, Dahlia; Rezky Putri Indarwati Abdullah (Sean Institute, 2024)
Gout disease has emerged recently, affecting the majority of people, not only the elderly but also young people. This is based on an unhealthy lifestyle that triggers the emergence of various diseases, one of which is gout. This study aims to determine the effectiveness of consuming boiled water from bay leaves (Syzygium polyanthum) in reducing uric acid levels. This research was carried out by collecting data from various sources, research journals conducted previously. The research results show that boiled bay leaf water can reduce uric acid levels because it contains several compounds such as essential oils, flavonoids and tannins. Flavonoids are secondary metabolite compounds that have the ability to prevent the formation of the xanthine oxidase enzyme. From these results, bay leaves are effective in reducing uric acid levels